Performance Modeling and Engineering - Liu, Zhen; Xia, Cathy H. (Springer US : Imprint: Springer, 2008)
This book presents the latest advances in methodology and techniques of performance modeling and engineering, ranging from theoretical advances to system and architecture developments, from technology to economics, from academic innovations to engineering processes, from statistical analysis to system control, and from enterprise systems to computer networks. The collection promotes innovative research in these emerging topics, bridging the gap between theory and practice, and stimulating the use of these new developments. Part I focuses on performance design and engineering, introducing new methodologies and considerations including machine learning, network economics, online advertising and performance engineering. Part II concentrates on scheduling and control, covering new developments in Internet traffic routing, network scheduling, and modeling and control of computer systems. Each chapter is self-contained, including both a broad survey of the topic and the technical challenges and solutions. Specific topics addressed include: reduction techniques that transform practical problems into well-studied machine learning problems, which can then be solved using existing base-learning algorithms Performance Engineering and Management Method (PEMM), which addresses the risks related to information technology performance, capacity and scalability economic models of communication and the importance of the economic impact on design choices the auction system for sponsored search advertising, including the mathematical and algorithmic issues and the challenges involved oblivious routing of Internet traffic, encompassing the deployment, performance guarantee, and various routing architecture and protocol issues in today's Internet design methods and analysis techniques of distributed scheduling algorithms in networks state-of-the-art insights into the application of control theory and optimization techniques on computer systems and computer networks Performance Modeling and Engineering provides new perspectives and establishes a connection between market mechanisms and Internet applications. Researchers in performance and evaluation and networking and systems will find that this book provides them with an understanding of both theoretical and practical issues, and allows them to develop both mathematical frameworks and engineering processes.